The labor market in Norway, 2000-2018 - Øivind A. Nilsen (IZA World of Labor, 2020)
Norway has a rather high labor force participation rate and a very low unemployment rate. Part of the reason for this fortunate situation is the so-called “tripartism”: a broad agreement among unions, employers, and government to maintain a high level of coordination in wage bargaining. This has led to downward real wage flexibility, which has lessened the effects of negative shocks to the economy. Reduced net immigration, especially from neighboring countries, also mitigated the negative effects of the oil price drop in 2014. A potential drawback of tripartism is the difficulty of reducing employee absences and disability.
Keywords: J3; J6; 330; wages; unemployment; Norway; gender equality; tripartism